2013
DOI: 10.1002/csr.1337
|View full text |Cite
|
Sign up to set email alerts
|

Motivations for Corporate Sustainability Management: Contrasting Survey Results and Implementation

Abstract: This paper compares empirical findings on the implementation of sustainability management with the results of earlier surveys on corporate motivations to deal with sustainability. We analyze the relevance of three different motivations, i.e. seeking corporate legitimacy, market success, and internal improvement. This is accomplished by matching these motivations with empirical findings on the engagement of functional areas. The underlying rationale is that differences in the engagement of functional areas can … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
158
0
4

Year Published

2013
2013
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 139 publications
(167 citation statements)
references
References 79 publications
5
158
0
4
Order By: Relevance
“…Many scholars have investigated CSR motives, and several typologies and inventories have been made [14,[16][17][18]33,[35][36][37][38]. However, few of these studies have linked the identified motives to actual firm behavior, focusing mostly on self-reported behavior in CSR reports and interviews [17].…”
Section: Theoretical Frameworkmentioning
confidence: 99%
See 3 more Smart Citations
“…Many scholars have investigated CSR motives, and several typologies and inventories have been made [14,[16][17][18]33,[35][36][37][38]. However, few of these studies have linked the identified motives to actual firm behavior, focusing mostly on self-reported behavior in CSR reports and interviews [17].…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…These instrumental theories have also been translated into practice, as can be seen by the instrumental motives for corporate social responsible behavior identified in empirical studies [17,33,36,38]. Motives that are categorized as instrumental are characterized as serving self-interest [9,14] and as being derived from external incentives and are thus extrinsic by nature [35,46].…”
Section: Instrumental Motivesmentioning
confidence: 99%
See 2 more Smart Citations
“…Where early contributions were focused on external factors, internal motivation and connecting drivers have gained in significance. Figure 1 gives an overview of the main motivational factors and drivers for corporate sustainability (Bansal and Roth 2000; van Marrewijk and Werre 2003; van Marrewijk 2003;Schaltegger and Burritt 2005;Epstein and Buhovac 2014;Windolph et al 2014;Lozano 2015;Engert et al 2016).Upon consideration of the motivations behind implementing sustainability into the corporate strategy, a new or adapted strategy has to be defined. In a procedural approach to strategy development, the main imperatives and courses of action are discussed in the following section.…”
mentioning
confidence: 99%